Characterization of Expression Quantitative Trait Loci in the Human Colon. Issue 2 (February 2015) - Singh, Tarjinder; Levine, Adam P.; Smith, Philip J.; Smith, Andrew M.; Segal, Anthony W.; Barrett, Jeffrey C.
Abstract : Background: Many genetic risk loci have been identified for inflammatory bowel disease and colorectal cancer; however, identifying the causal genes for each association signal remains a challenge. Expression quantitative trait loci (eQTL) studies have identified common variants that induce differential gene expression and eQTLs can be cross-referenced with disease association signals for gene prioritization. However, the genetics of gene expression are highly tissue-specific, and further eQTL datasets from primary tissues are needed. Methods: We have conducted an eQTL discovery study using tissue extracted endoscopically from the terminal ileum and 4 colonic locations of non-inflamed bowel from 65 controls and patients with quiescent inflammatory bowel disease. A genome-wide cis -eQTL analysis was performed on >3, 600, 000 variants and 13, 558 expressed probes. Results: We identified 1312 independent eQTLs associated with the differential expression of 1222 genes in rectal mucosa. One hundred seventy-one, 211, 168, and 102 independent eQTLs were identified in the sigmoid, descending colon, ascending colon, and terminal ileum, respectively. Twenty-six percent of genes with rectal eQTLs were novel and unique compared with 7 published eQTL datasets. Rectal eQTLs were significantly enriched for genes expressed in the colon. Examining 163 inflammatory bowel disease risk loci identified 11 tag single-nucleotide polymorphisms that were rectal eQTLs. A colorectal cancer locus at 11q23 contained a rectal eQTL for COLCA2, a protein implicated in colon cancer pathogenesis. Conclusions: This study defines a catalog of ileal and colonic eQTLs. Our data reaffirm the tissue specificity of eQTLs and support the notion that identification of functional variants in relevant tissue can be effective in fine-mapping genetic risk loci. Abstract : Article first published online 7 January 2015.Supplemental Digital Content is Available in the Text.